Efficient Lossless Data Compression Using Adaptive Arithmetic Coding - Sudhamsu, Gadug; Singh, Shweta; Gautam, Chandra Kant (International Conference on Computing, Communication, and Networking Technologies (Online), 2024)
Efficient Lossless Records Compression AdapuseAritadaptive arithmetic coding approach uses an entropy coder to safely and appropriately encode facts. This method works by supplying a frequency distribution for symbols or characters in textual content documents with extra concise and green output. If the information must be compressed without losing records, then the compression rate can be managed by changing mathematics coding techniques. The approach can get a remarkably optimized compression rate by employing a statistical method that takes relative frequencies for every character/symbol into attention, no matter in what permutation the symbols are used within the file. Also, a faster version of Adaptive arithmetic Coding can be employed for large datasets that would otherwise be difficult to compress using traditional compression methods. For this reason, it was shown that the technique effectively reduces data volume while maintaining an acceptable level of accuracy..